Comparison of policies of emergency lateral transshipment for inventory systems - Ee, Chin Yuan (2011)
With the increasing air travel, the stocking of service parts at various airline bases and depots becomes crucial. Inability to meet demands for service parts will result in delays and inevitably lead to increased costs for the airlines. As such, there is a need for optimal inventory policies and systems. This project compares some inventory policies with regard to emergency lateral transshipment through simulation modelling.